2023
DOI: 10.1242/dmm.049699
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pancreatic neoplasia in the KRAS/TP53 Oncopig

Abstract: Five-year survival of pancreatic cancer (PC) remains low. Murine models may not adequately mimic human PC and can be too small for medical device development. A large animal PC model could address these issues. We induced and characterized pancreatic tumors in Oncopigs (transgenic swine containing KRASG12D and TP53R167H). Oncopigs underwent injection of adenovirus expressing Cre recombinase (AdCre) into one of the main pancreatic ducts. Resultant tumors were characterized by histology, cytokine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[The following sec#on may be included in the final drap] Our technique for inocula#ng the Oncopig pancrea#c duct [5] ensures targeted delivery of the adenoviral vector Ad-K8-Cre. This method contrasts with tradi#onal systemic or parenchymal delivery methods, which open result in less specific targe#ng and variable efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[The following sec#on may be included in the final drap] Our technique for inocula#ng the Oncopig pancrea#c duct [5] ensures targeted delivery of the adenoviral vector Ad-K8-Cre. This method contrasts with tradi#onal systemic or parenchymal delivery methods, which open result in less specific targe#ng and variable efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The insidious onset of PDAC, where early stages are typically asymptomatic, presents significant challenges for detection and effective intervention. In our previous study we employed transgenic porcine model expressing the KRAS^G12D mutation [5], a prevalent oncogenic driver in PDAC, to elucidate the mechanisms of tumorigenesis and evaluate final-stage intervention strategies. The Cre-Recombinase dependent expression of this mutation allowed us for exploring of Pancreatic Cancer pathogenesis, offering insights into the initiation and progression of neoplastic transformations within the pancreas [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR technology has been widely used for conditional regulation of gene expression in a variety of animals, including pig models [16, 37–42, 57–59]. For conditional activation of gene expression, conditional cassettes have been set in variants of two basic designs: promoter‐loxP‐STOP‐loxP‐GOI (LSL) and promoter‐loxP‐lox2272‐inverse GOI‐inverse loxP‐inverse lox2272 (FLEX) [40, 41, 60–64] as shown in Figure 2.…”
Section: Swine Models With Recombinase‐specific Recognition Elementsmentioning
confidence: 99%
“…A comprehensive understanding of the genomic relatedness between humans and other mammals is necessary to evaluate the common pathways and functional similarities and the appropriateness of using different animal models to study human diseases. Although the mouse is the most commonly used animal model in the study of human diseases [1], its smaller size and lifespan and differences in the latency periods for diseases [2], drug metabolism [3], inflammatory response [4], and other processes [5][6][7][8] suggest the need to identify animal models with more disease-relevant similarities to humans for the study of human diseases. A comparison of genomic sequences among human, mouse, and pig genomes indicated that pig sequences were closer to the human sequences, with greater numbers of ultra-conserved regions compared to the mouse genome [9][10][11].…”
Section: Introductionmentioning
confidence: 99%